Venture Capital Industry Index Portfolio Analysis - Dagang Yang; Xuefeng Wang; Yishi Zhu (Institute of Advanced Engineering and Science, 2013)
This paper using index analysis method, knowledge of venture capital as well as index funds investment ideas, successively set up the Markowitz model and the single index model of index investing. Markowitz model for the calculation of the risk of workload is too big and single-index model although accuracy is slightly lower, but can certainly be very well used in practice. Therefore, We use index invest to invest in Shanghai 10 index securities with the single-index model , and apply lingo software to figure out the venture capital portfolio which have different yields. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2454